Evolutions in the management of non-small cell lung cancer: A bibliometric study from the 100 most impactful articles in the field - Chen, Siyuan; Qiao, Yu; Chen, Juan; Li, Yanan; Xie, Jianlian; Cui, Pengfei; Huang, Ziwei; Huang, Di; Gao, Yiming; Hu, Yi; Liu, Zhefeng (Frontiers in Oncology, 2022)
Objective: The study was designed to explore the evolution of non-small cell lung cancer (NSCLC) management in the last 20 years. Methods: The top 100 most-cited papers on NSCLC treatment were retrieved from the Web of Science Core Collection database. R and VOSviewer were used to extract bibliographic information, including the year of publication, countries/regions, institutions, authors, journals, keywords, impact factor, and total citations. The topic and type of papers were checked independently by authors. Bibliometric analysis was conducted and visualized with R, CiteSpace, Excel and VOSviewer to identify output dynamics, research forces, topics, hotspots, and frontiers in the field. Results: The average citation of each retrieved top 100 most-cited NSCLC management papers was 1,725 (range: 615-7,340). Fifty-seven corresponding authors were from the United States. This country contributed the most papers (n=76), followed by Germany (n=34), France (n=33), and South Korea (n=32). The top contributors were Paz-Ares L. (n=12) and Reck M. (n=12). The Memorial Sloan Kettering Cancer Center published the largest number of papers (n=20). There were two significant citation paths, indicating publications in medicine/medical/clinical journals primarily cited journals in molecular/biology/genetics fields, partly cited health/nursing/medicine fields. Top-cited papers mainly came from the New England Journal of Medicine (n=33, citations=80,427), followed closely by the Journal of Clinical Oncology (n=28, citations=32,408). “Chemotherapy” (n=36) was the keyword with the greatest frequency of co-occurrence. “Open-label” was the keyword with the strongest burst strength (=4.01), followed by “nivolumab” (=3.85), “blockade” (=2.86), and “efficacy” (=2.85). Conclusions: The United States as a nation and the Memorial Sloan Kettering Cancer Center as an institute contributed the most to this field. The New England Journal of Medicine is the most eye-catching journal. Hotspots of NSCLC management have almost undergone an evolution from chemotherapy and radiotherapy to targeted therapy to immunotherapy. Molecular/biological/genetic fields become the main research base for NSCLC treatment. Immunotherapy and combination therapy are research frontiers.